Model Penentuan Ukuran Batch Produksi dan Bufferstock untuk Sistem Produksi Mengalami Penurunan Kinerja dengan Mempertimbangkan Perubahan Order Awal - Ivan D Wangsa (Jurnal Optimasi Sistem Industri, 2015)
This study develops a model that involves information the preliminary order. At first, the manufacturer provides the preliminary order for the coming week (five days) varies from day to day and is received on Friday. Change in the preliminary order for a given day is announced one day before and this is viewed as it occurs randomly. Moreover, production systems experience performance degradation (deterioration). Status of the production process shifts from in control to out of control that is identified by the last inspection. Inspection is done by sampling. At the time of the status of out of control the probability of producing non-conforming system component that is charged to the restoration cost and warranty costs.This paper is looking for a solution for determining the production batch size and the buffer stock to reduce total cost. The decision variables are production run period (T) and buffer factor (m). Having obtained the variables T and m, then the variable production batch size (QT) and the buffer stock (BT) can be determined sequentially. Heuristic methods used are Silver-Meal (SM) and Least Unit Cost (LUC) to obtain a solution for each model. Numerical examples are given to demonstrate the performance of the models. From the numerical results, it appears that LUC method is better than SM method.